Fluorescein as an artificial enzyme to mimic peroxidase. Issue 96 (14th November 2016) - Liu, Li; Shi, Ying; Yang, Yufang; Li, Menglu; Long, Yijuan; Huang, Yuming; Zheng, Huzhi
Abstract : Fluorescein was found to possess intrinsic peroxidase-like activity, which could catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by H2 O2 to produce a color reaction. Abstract : Fluorescein was found to possess intrinsic peroxidase-like activity, which could catalyze the oxidation of 3, 3′, 5, 5′-tetramethylbenzidine (TMB) by H2 O2 to produce a color reaction. It opens the possibility of using such small molecules as peroxidase-like catalysts.